THE PROCESS OF ENSURING THE TRANSPARENCY OF STATE POWER INSTITUTIONS AND ITS SPECIFIC FEATURES - Khudoberdiyev Jamoliddin (Galaxy International Interdisciplinary Research Journal, 2024)
In democratic societies, the openness and transparency of state institutions is important. Developed and developing countries are increasingly recognizing that free access to information is a cornerstone of democracy. Whether we’re talking about the government or private companies that run public services, access to the data of these organizations means increased accountability and allows citizens to know what these organizations are doing and what they’re using public money for. The use of information on the activities of state power institutions increases citizens’ confidence in state institutions, allows citizens to understand state policy decisions and control their implementation. The openness and transparency of the activities of the institutions of state power is an important indicator of the effective implementation of the powers assigned to them, an indispensable condition for the establishment of a socio-legal state model, which cannot be implemented without the constant cooperation of citizens and authorities. The fact that the principle of openness is strengthened in many regulatory legal documents at the federal and regional levels increases its effectiveness. In a democratic state, it is a priority to increase the openness of state power institutions. Openness and transparency of the activities of state power institutions serve to increase citizens’ trust in state bodies, reduce administrative obstacles and cases of corruption. The activity of state authorities is closed to citizens, it limits public control over their activities, it is characterized by the underdevelopment and low effectiveness of the procedures for ensuring the openness of state institutions. These problems lead to the strengthening of administrative barriers, the lack of transparency of the activities of executive authorities, and the low assessment of the effectiveness of the entire state management system by citizens.[2] In the process of ensuring the openness and transparency of the activities of the institutions of state power, it is important to strengthen the rights of citizens regarding freedom of information, to increase the responsibility of state bodies to the general public, and to establish a system of regularly informing citizens about the main directions of state policy.